Dr. Robert (Bob) DeMott
Doctor Robert (Bob) DeMott with unknown woman in the Steinbeck Research Center, now the Martha Heasley Cox Center for Steinbeck Studies, (MHCCfSS). This is the original location on the 6th floor of the Wahlquist Library at San Jose State. Original in safe